Pengaruh Pembelajaran Aqidah Akhlak Terhadap Etika Siswa di MTs - Purba, Fitri Rahmawati Br; Dahlan, Zaini (Institut Syekh Abdul Halim Hasan Binjai, 2025)
Learning moral aqidah at Madrasah Tsanawiyah (MTS) has an important role in forming students' strong character and integrity in accordance with Islamic teachings. This study aims to fill gaps in previous research by exploring more effective and in-depth learning methods, as well as analyzing the factors that influence learning outcomes. A mixed approach that integrates quantitative and qualitative analysis is used to understand the influence of moral aqidah learning on student ethics at MTS. The results of the study show that there is an increase in students' understanding of religious and moral values after taking part in moral aqidah learning. The discussion combines research findings with theoretical review highlighting the role of factors such as teaching quality and learning environment in shaping learning effectiveness. The conclusion confirms that learning moral aqidah provides a significant positive impact on student character, while suggestions are provided for further development in the learning context at MTS.